2011
DOI: 10.1039/c1jm10244c
|View full text |Cite
|
Sign up to set email alerts
|

Converting AgCl nanocubes to sunlight-driven plasmonic AgCl : Ag nanophotocatalyst with high activity and durability

Abstract: Uniform AgCl nanocubes with an average edge length of 85 nm have been prepared by a facile reverse micelle method. Partially reducing the as-produced AgCl nanocubes enables us to achieve a class of sunlight-driven plasmonic AgCl : Ag nanophotocatalysts. The optical absorption spectrum of the thusachieved nanophotocatalyst exhibits strong absorption in the visible region due to surface plasmon resonance (SPR) of silver nanoparticles. Under sunlight illumination the hybrid AgCl : Ag nanoparticles exhibit high ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…41b-d, 57 Using an in situ ion exchange reaction between BiOBr microspheres and AgNO 3 followed by photoreduction, Cheng et al 41b synthesized visibleresponsive Ag/AgBr/BiOBr hybrid photocatalyst. It was found that the reaction rate constant for MO decomposition on Ag/ AgBr/BiOBr is 0.396 min À1 , much higher than that of Ag/AgBr (0.024 min À1 ) and N-P25 (0.007 min À1 ).…”
Section: Mineralization Of Organic Pollutantsmentioning
confidence: 99%
“…41b-d, 57 Using an in situ ion exchange reaction between BiOBr microspheres and AgNO 3 followed by photoreduction, Cheng et al 41b synthesized visibleresponsive Ag/AgBr/BiOBr hybrid photocatalyst. It was found that the reaction rate constant for MO decomposition on Ag/ AgBr/BiOBr is 0.396 min À1 , much higher than that of Ag/AgBr (0.024 min À1 ) and N-P25 (0.007 min À1 ).…”
Section: Mineralization Of Organic Pollutantsmentioning
confidence: 99%
“…Many growth techniques and methods have been applied toward the fabrication of Ag/AgX heterostructures. Ag nanoparticles decorated on the surface of semiconductors are mainly prepared using different methods depending on the source of Ag nanoparticle used and include: i) The colloid route, ii) the reduction of metal salts, iii) template‐directed protocols using a surfactant or in situ self‐assembly method, iv) chemical reduction, v) ultrasonic spray pyrolysis methods, and vi) thermal‐or light‐induced reduction of AgX and to generate metallic Ag particles on the surface of the AgX substrate. Very recently, Mao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches and methods have been proposed for developing multicomponent hybrid nanomaterials with diverse chemical compositions and morphologies that not only have the original properties of the components but also have new properties derived from the incorporation of each component [6][7][8][9][10][11][12][13][14] . Furthermore, the catalytic performance of hybrid nanomaterials has been found to be remarkably superior to that of single-component nanomaterials in diverse reactions.…”
Section: Introductionmentioning
confidence: 99%